Spatiotemporal Characterization of Anterior Segment Mesenchyme Heterogeneity During Zebrafish Ocular Anterior Segment Development - Van Der Meulen, Kristyn L.; Vöcking, Oliver; Weaver, Megan L.; Meshram, Nishita N.; Famulski, Jakub K. (Frontiers in Cell and Developmental Biology, 2020)
Assembly of the ocular anterior segment (AS) is a critical event during development of the vertebrate visual system. Failure in this process leads to Anterior Segment Dysgenesis (ASD), which is characterized by congenital blindness and predisposition to glaucoma. The anterior segment is largely formed via a neural crest-derived population, the Periocular Mesenchyme (POM). In this study, we aimed to characterize POM behaviors and transcriptional identities during early establishment of the zebrafish AS. Two-color fluorescent in situ hybridization suggested that early AS associated POM comprise of a heterogenous population. In vivo and time-course imaging analysis of POM distribution and migratory dynamics analyzed using transgenic zebrafish embryos (Tg[foxc1b:GFP], Tg[foxd3:GFP], Tg[pitx2:GFP], Tg[lmx1b.1:GFP], and Tg[sox10:GFP]) revealed unique AS distribution and migratory behavior among the reporter lines. Based on fixed timepoint and real-time analysis of POM cell behavior comprehensive model for colonization of the zebrafish AS was assembled. Furthermore, we generated single cell transcriptomic profiles (scRNA) from our POM reporter lines and characterized unique subpopulation expression patterns. Based on scRNA clustering analysis we observed cluster overlap between neural crest associated (sox10/foxd3), POM (pitx2) and finally AS specified cells (lmx1b, and foxc1b). scRNA clustering also revealed several novel markers potentially associated with AS development and/or function including lum, fmoda, adcyap1b, tgfbi and hmng2. Taken together, our data indicates that AS-associated POM, or Anterior Segment Mesenchyme (ASM), is not homogeneous but rather comprised of several subpopulations with differing colonization patterns, migration behavior, and transcriptomic profiles.